150k views
0 votes
Help with #5 please!! explain thoroughly ): f(x) = 3x + 2g(x) = -x + 10

Help with #5 please!! explain thoroughly ): f(x) = 3x + 2g(x) = -x + 10-example-1

1 Answer

5 votes

From "Exemple 3", we know that, for x = 2, f(x) = g(x).

And the y coordinate of point with x = 2 is the value of the function at x = 2:

y = f(2) = g(2)

So, one way to find the y-coordinate, is by replacing x by 2 in the expression for f(x) = 3x + 2:

y = f(2)

= 3 * 2 + 2

= 6 + 2

= 8

Another way to do so is by replacing x by 2 in the expression for g(x) = -x + 10:

y = g(2)

= -2 + 10

= 10 - 2

= 8

User NawK
by
4.9k points